Strategi Komunikasi Pengadaan Calon Aparatur Negara di Kota Serang - Nadifi Silviana Pramesti; Titi Stiawati; Ipah Ema Jumiati (Publikasi Indonesia, 2023)
The communication strategy used determines the success of a communication. The communication strategy itself involves good planning and management, if the communication strategy fails it can have negative consequences. Procurement of CASN aims to obtain apparatus human resources that fill gaps or needs for the formation of position in the Serang City Environment that are clean and have basic competencies and fields that match the needs, work requirements and role as leaders of the state government in accordance with the nature of ASNs whose mission is to provide service to society. Based on the little that the researcher adopted, namely the Communication Strategy for Procurement of Candidates for State Civil Servants in the City of Serang, the research method was qualitative research. This study obtained data from digital observation results, interviews with informants who were considered to be in charge of and in charge of these activities and interviewed one of the participants who took part in the CASN selection in Serang City who passed in 2021 as well as official document documentation. The communication strategy used by the Serang City BKPSDM in the Procurement of Candidates for State Civil Servants is to disseminate information via websites and social media. However, the role of the website bkpsdm.serangkota.go.id is very active. The success of the communication strategy carried out by the Serang City BKPSDM wes seen from website visitors, social media, selection applicants, and selection participants in the later stages where almost all participants took part.